Influence of gender, ethnicity and makeup on age estimation by adults in the community - Barnett, Rosalind (2018)
Recent history has witnessed an emerging social issue concerning children and teenagers appearing older than their age, reasons for which may include clothing, makeup, false identification, dating websites or social media. This has ramifications for statutory rape, whereby a sexual act takes place involving a person under the age of consent, since many perpetrators claim they were unaware of their sexual partner’s age before participating. The current study investigated the ability of adults in the community to estimate the age of Asian and White 12, 14, 16 and 18-year-olds, with reference to the age, gender, and ethnicity of the participant and model, as well as the influence of makeup. Participants were exposed to photographs of 12 models at each age, whilst each female was presented once more with makeup. Participants were required to estimate the models’ age in a within-subjects design. Results showed that participants overestimated the age of all age-groups, with an average of 3.07 years older than the actual age. Paired samples t-tests found that this was most pronounced for White female and Asian male models, and females between 12 and 16-years-old with makeup on. Results of one-way ANOVA’s found that participant gender and age had no effect, but found significant differences between Asian and White participant responses. The study concluded that people cannot accurately estimate age using only facial cues, and that model gender, ethnicity and makeup, and participant ethnicity, significantly impact perceptions. This study has implications for the application of statutory rape laws and victim protection.